The two goats (Malaysia : Mind to mind, 2018)
The "Two Silly Goats" story for preschoolers is about two goats who encounter each other on a narrow bridge and refuse to back down, leading to a fight that ends in both of them falling into the river and drowning. The moral of the story is that foolishness is often punished. Another version of the story features two goats who, instead of fighting, one wisely lies down allowing the other to pass safely. This version teaches that wise people find solutions over conflict.
Location: 3C
Keywords: Story book